THE JURIDICAL REVIEW OF THE IMPLEMENTATION OF SUPREME COURT REGULATION CONCERNING GUIDELINES FOR ADJUDICATING MARRIAGE DISPENSATION - Trubus Wahyudi; Sutrisno Sutrisno (Jurnal Pembaharuan Hukum, 2022)
This reseach aims to know the law enforcement paradigm relating to adjudicating cases of marriage dispensation applications as the implementation of Perma Number 5 of 2019 is part of the litigation task that must be carried out by the judiciary as a form of a case settlement which is a community need for justice seekers for the sake of upholding the law supremacy and justice in Indonesia. Normatively the legal arrangements for the Marriage Dispensation case are Article 7 of Act No. 1 of 1974 concerning Marriage, Act No. 16 of 2019 concerning the First Amendment of Act No. 1 of 1974, Article 7 of the Compilation of Islamic Law, and Regulation of the Supreme Court (PERMA) Number 5 of 2019 concerning Guidelines for Adjudicating Marriage Dispensation Applications. This study used a sample of several decision objects in certain Religious Courts in the jurisdiction of the Central Java Religious High Court, through a series of research methods with a sociological juridical or Social legal Research, and data collection techniques through interviews and library studies as well as several Religious Court decisions regarding inkracht (permanent) Marriage Dispensation. In this study, aspects of the examination of the Marriage Dispensation case were revealed by the judges in exploring substantive reasons related to the age of children who are not old enough to marry according to the law. The result shown that the implementation of Perma Number 5 of 2019 regarding Guidelines for Adjudicating Marriage Dispensation Applications in Religious Courts can be formulated in the form of a dictum,"Declaratives” as a court product and what are the legal consequences regarding the stipulation of a Marriage Dispensation by the Court which functions to benefit, justice, and fair legal certainty.